Quantum effects in trapped beryllium ions - Feng,X; Hernandez-Pozos,JL; Vincent,J; Walker,T; Segal,DM; Thompson,RC (1996)
Two experiments looking at the different aspects of the quantum theory of the interaction of radiation with atoms (ions) are reported. The first experiment investigates the quantum Zeno effect in which an atomic transition is `slowed down' by repeated measurements of the state of the system. The second experiment takes advantage of the unique properties of trapped ions to study cavity quantum electrodynamics (QED) effects, in particular, the modifications to the spontaneous emission of trapped ions held at the center of an optical cavity. The magnitude of the cavity's effect on the atomic emission increases with decreasing cavity mode volume so that small cavities and hence small traps are needed.